Wide-bandgap lanthanide niobates: Optical properties and applications - Dwivedi A.; Singh A.K.; Singh S.K. (My University, 2025)
Niobate phosphors (ANbO4; A: Y, Gd, La) are fascinating wide-bandgap materials which attracts vast interest and vital applications. These compounds exhibit fergusonite crystal structure and give broad-band self-activated emission due to ligand to metal charge transfer band from O2− to Nb5+ ions. Presence of Bi3+ in ANbO4 creates low lying new states (due to metal to metal charge transfer state of Bi3+ to Nb5+ ions) and changes crystal field, which enhances overall intensity of the self-activated luminescence. The self-activated emission of ANbO4 sensitizes dopant ions in them, particularly trivalent lanthanides, which emanate luminescence in different spectral region and open enormous application for this host. Aim of this review is to pinpoint suitable synthesis technique of ANbO4 phosphor, highlight the current understanding of their crystal structure and optical behavior, and to discourse their vital technological applications. A concise summary and prospective is also covered to signpost the future research directions. © 2020 Elsevier Ltd